Development of an empirical dust storm attenuation model for microwave links in arid area - Ahmed, Elfatih AbdelRahman (Kulliyyah of Engineering, International islamic University Malaysia, 2017)
Currently, wireless communication service providers are using higher and higher frequencies because of the congested frequencies spectrum and opportunity to deliver high-capacity. However, higher frequency bands are more sensitive to weather condition and atmospheric particles. Microwave signal attenuation due to dust storm is one of those potential problems and need to be investigated in order to provide reliable wireless communication services in arid areas. Few dust storm attenuation prediction models have been developed recently based on scattering theory, numerical methods and approximation of dust properties. None of these models could predict measured attenuations at different frequencies in arid areas. Actually dust storm is a complex phenomenon which is difficult to be described by the theoretical physical or mathematical models. Hence an empirical modelling based on the statistical observations of dust storm properties and its corresponding microwave signal levels is proposed in this thesis. Visibility, humidity and wind speed and their effects on five operational microwave links at 14 GHz and 21 GHz frequencies with different path lengths were measured for one year period at Khartoum, Sudan. From measurement, it has been observed that dust storms is accompanied by rapid increase in relative humidity which affects the dielectric constant of the dust and consequently, obvious degradation in the signal level. It is obvious that the higher frequency is more affected than the lower and more than 10 dB difference is observed between 14 and 21 GHz links with almost same path lengths and same visibilities. Measured specific attenuation in dB/Km for both 14 and 21 GHz are compared at the same visibility condition to the predicted attenuations using six available prediction models. But the available models are completely incapable to predict the measured attenuation at both 14GHz and 21GHz. An empirical model has been developed as a function of visibility, frequency, moisture content and dielectric constant to predict specific attenuation in dB/Km. The measured specific attenuation at 21 GHz, measured visibility and the frequency dependency relation of the dielectric constant of sand with moisture content have been correlated to develop the model. The proposed model has been validated at 7.5 GHz, 13 GHz, 14 GHz, 21GHz and 40 GHz with measurements in different locations. The proposed model reflects all measurements more accurately than contemporary physical and mathematical models. The proposed empirical model is simple in its expression and is characterized by the flexibility in accommodating a wide frequency ranges and different moisture levels. A path length adjustment factor has also been proposed in order to predict total attenuation for longer links. The proposed adjustment factor is developed based on the exponential representation of the dust storm and the measured attenuation at 14 GHz and 22 GHz with 7.6 km and 6.3 Km links. Fade margin has been analysed based on the proposed total attenuation prediction model and measured visibility statistics at Khartoum, Sudan and the microwave links data. It has been realized from the analysis that 99.99% reliability can be achieved only for 4.26 km, 2.8- km and 1.8 km links at Ku , Ka and V bands respectively, at 40 dB fade margin. All these findings will be very useful to design highly reliable microwave links operating at higher frequencies in arid areas.